Developing an Integrated Framework for Assessing the Life Cycle Greenhouse Gas Emissions and Life Cycle Cost of Buildings. (2017) - Schmidt, Monique; Crawford, Robert H.
Abstract: With building-related greenhouse gas emissions(GHGE) having more than doubled since 1970, they represent one of the largest and most attractive opportunities for climate change mitigation. However, current focus has mainly been on reducing operational GHGE leaving building embodied GHGE (i.e. the GHG emissions associated with the extraction, manufacture and transportation of materials, and the building construction process itself) largely ignored. These embodied emissions have been estimated to represent between 10% to 97% of a buildings total life cycle GHGE. It is thus critical that decision-making in relation to buildings is based on a life cycle perspective. One of the main barriers to this approach is the uncertainty surrounding the financial implications of life cycle GHGE reduction strategies. Despite project cost being a key driver for decision-making, building developers, designers and owners have insufficient knowledge or appropriate tools to adequately consider these life cycle costs and balance them against GHGE savings. Several methods exist for quantifying the costs of a building, such as life cycle costing (LCC). However, LCC and life cycle GHGE assessments are often used in isolation. This study will address the urgent need to move towards integrating these assessments by developing a framework that can be used to ascertain the important relationships and trade-offs between financial and GHGE performance of various building-related GHGE reduction strategies. This framework can be used as part of the building decision-making process and help create a low carbon, affordable built environment.